Students’ emotional engagement in online collaborative writing through google document - Rahmadania Putri Ferdianawati Iskandar; Muhammad Reza Pahlevi (Universitas PGRI Semarang, 2021)
Learning writing has been conducted by using various methods. Collaborative writing is one of method that used in writing learning practice. Studies about collaborative writing reveal that online collaborative writing is effective to promote students’ writing quality. There are many previous studies have explored the students’ perception, effectiveness, and benefits of collaborative writing. However, the study about students’ emotional engagement in collaborative writing is limited. This study aims to explore students’ emotional engagement during online collaborative writing through Google Docs. The exploration of students’ emotional engagement is beneficial to understand students’ feelings and emotions during the learning process. Classroom Action Research is used as the research design of the study. Participant of the research is four eleven grade high school students. The research was conducted at the SMA Negeri 1 Cikarang Barat in three weeks. Semi-structured interview and documentation were used for collecting the data. The result of the study showed that online collaborative writing through Google Docs involves students to learn writing enthusiastically. Online collaborative writing also involves students cognitively by acquiring new vocabulary during the online collaborative writing activity.